Sustainable development? A brief contrast between the discourse and reality in the colombian case (Revista cientifica In Vestigium Ire, 2020)
This work proposed to show how the discourse on sustainable development goes in a direction contrary to that of the actions that are taken on the matter, affecting the planet and promoting climate change. In this sense through the use of the deductive method with comparative analysis, it was proposed to demonstrate that Colombia does not escape that reality, and despite its environmental court policy constitution, environmental regulation in the country is far from consistent with the problems that the country faces, especially since its traditional economic model has been based on the exploitation of natural resources. For this reason, a real shift from discourse to action at the international and national levels is proposed to counteract the effects of climate change while continuing to generate wealth, but in a truly sustainable process.
Keywords: Sustainable development; climate change; environmental policy; awareness raising